Exploration et mission au Zanguebar - Jean-Michel Vasquez (Belgeo)
The aim of this presentation is to highlight the crucial part played by geographical exploration in the missionaries’ goal to territorialise their missions. Father Alexandre Leroy is a case in point when it comes to sub-Saharan Africa, that dreamed-up, coveted land which was sometimes even explored in the 19th century. From 1877 to 1892, during his time in Zanguebar (Eastern Africa) as a missionary from the Congregation of the Holy Heart of Mary, he undertook numerous exploratory journeys and systematically wrote articles as well as drew sketches and maps to report on what he had seen. His work was most appreciated by the readers of the edifying publications of his time. The sum of geographical, ethnological and zoological information he left behind regarding that area was long to remain unequaled. This presentation will use his maps first to assess the extent and quality of the geographical data gathered by missionaries and secondly to consider the many ways they were put to use as tools for the apostolate, so as to understand how the space of the mission - which remains first and foremost a Christian territory in the making- is shaped.